2022
DOI: 10.1371/journal.pone.0262294
|View full text |Cite
|
Sign up to set email alerts
|

Improved biomechanics in experimental chronic rotator cuff repair after shockwaves is not reflected by bone microarchitecture

Abstract: Purpose The aim of this study was to investigate the effect of extracorporeal shockwave therapy (ESWT) on bone microstructure as well as the bone-tendon-interface and the musculo-tendinous transition zone to explain the previously shown improved biomechanics in a degenerative rotator cuff tear animal model. This study hypothesized that biomechanical improvements related to ESWT are a result of improved bone microstructure and muscle tendon properties. Methods In this controlled laboratory study unilateral su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Feichtinger et al revealed that ESWT signi cantly improves the load-tofailure results in rats after rotator cuff tear repair. Moreover, they found that ESWT does not affect bone microstructure [27,28]. In their examination of gene expressions, speci cally CXCL12 (C-X-C motif chemokine 12), TGF-β1 and TGF-β3 (transforming growth factor beta 1 and 3), and VEGFR2 (vascular endothelial growth factor receptor 2), Feichtinger et al found no signi cant differences [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feichtinger et al revealed that ESWT signi cantly improves the load-tofailure results in rats after rotator cuff tear repair. Moreover, they found that ESWT does not affect bone microstructure [27,28]. In their examination of gene expressions, speci cally CXCL12 (C-X-C motif chemokine 12), TGF-β1 and TGF-β3 (transforming growth factor beta 1 and 3), and VEGFR2 (vascular endothelial growth factor receptor 2), Feichtinger et al found no signi cant differences [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they found that ESWT does not affect bone microstructure [27,28]. In their examination of gene expressions, speci cally CXCL12 (C-X-C motif chemokine 12), TGF-β1 and TGF-β3 (transforming growth factor beta 1 and 3), and VEGFR2 (vascular endothelial growth factor receptor 2), Feichtinger et al found no signi cant differences [27,28]. However, histological changes in structures other than bone microstructure, and the speci cs of gene expression alteration by ESWT, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical removal of the calcification may lead to side effects in the soft tissue of the heel [ 14 ]. f-ESWT therapy results in the reduction or complete disappearance of the calcification, while the level of the patient's discomfort experienced during application is the lowest compared to other treatment options [ 15 ].…”
Section: Introductionmentioning
confidence: 99%